Analisis Operasional dan Tindakan Preventif terhadap Eskalasi Angka Kematian Jemaah Haji Tahun 2023 - Hashifah, Ghina Izzatul; Anasom, Anasom (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
This study aims to analyze the challenges faced during the operational implementation of the 2023 Hajj pilgrimage and to identify preventive measure for the upcoming years. The research employs a qualitative approach, with primary data in the form of mortality data of 2023 pilgrims processed by Siskohatkes-Kemenkes. Meanwhile, secondary sources are derived from interviews with 2023 Hajj pilgrims and various electronic media sources. The results finding indicate that the peak of pilgrim deaths occurred in Muzdalifah, where many pilgrims suffered from dehydration while waiting for transportation to Mina. The incident started on the 10th of Dzulhijjah, allegedly due to non-Hajj visa holders were overcrowding the Taraddud routes, causing congestion in the pickup fleets. Additionaly, accommodation services and support for the elderly pilgrims were not to be insufficient. To prevent similar incident in the future implementations, the Ministry of Religious Affairs has designed various presentive measures, including Murur and Tanazul stays to hotels, deemed appropriate steps in improving pilgrim safety. This research is expected to provide significant contributions to the government and relevant authorities as an evaluation material for better Hajj management in the future.